2013
DOI: 10.1080/0972060x.2013.793971
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Composition of the Essential Oils of Aerial Parts and Flowers ofChromolaena odorata(L.) R. M. King & H. Rob. from Western Ghats Region of North West Karnataka, India

Abstract: Abstract:The chemical composition of the essential oils of aerial parts and flowers of Chromolaena odorata (L.) R. M. King & H. Rob., collected from Western Ghats region, were obtained by hydrodistillation and analyzed by gas chromatography (GC) and gas chromatography/mass spectrometry (GC-MS). Fifty two and thirty four compounds were identified from aerial parts and flowers, representing 94.9 % and 95.2 % of the total oils, respectively. The essential oil from aerial parts was dominated by pregeijerene (14.2 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(20 citation statements)
references
References 9 publications
(13 reference statements)
1
17
0
2
Order By: Relevance
“…The relatively high heritability coefficients calculated for some essential oil components informing whether a character is more influenced by genetic or other factors, confirm that the potential to produce a certain chemical pattern is genetically coded, but the gene expression will be induced or repressed by environmental factors also (Franz, 1993). The presence of geijerene and pregeijerene from the essential oil of the leaves C. odorata has also been reported quantitatively different in various countries (Bedi, Tonzibo, & Nguessan, 2001;Bedi, Tonzibo, Chopard, Mahy, & Nguessan, 2004;Joshi, 2013c;Owolabi et al, 2010;Pisutthanan et al, 2006). This study also found that the major compounds of P. mollis were the same with quantitative differences.…”
Section: Discussionsupporting
confidence: 56%
“…The relatively high heritability coefficients calculated for some essential oil components informing whether a character is more influenced by genetic or other factors, confirm that the potential to produce a certain chemical pattern is genetically coded, but the gene expression will be induced or repressed by environmental factors also (Franz, 1993). The presence of geijerene and pregeijerene from the essential oil of the leaves C. odorata has also been reported quantitatively different in various countries (Bedi, Tonzibo, & Nguessan, 2001;Bedi, Tonzibo, Chopard, Mahy, & Nguessan, 2004;Joshi, 2013c;Owolabi et al, 2010;Pisutthanan et al, 2006). This study also found that the major compounds of P. mollis were the same with quantitative differences.…”
Section: Discussionsupporting
confidence: 56%
“…C. odorata or Siam weed is a scrambling perennial shrub which grows to 2-3 m in height with straight, pithy, brittle stems that branch readily. Phytochemical analysis has shown that C. odorata contains flavonoids 10 , terpenoids 11 , alkaloids 12 , essential oils 13 , tannins, and saponins 14 . The traditional uses or phytochemical properties of C. odorata are anticancer 15 , antidiabetic 16 , anti-inflammatory 17 , antimicrobial 18 , and antioxidant activities…”
Section: Introductionmentioning
confidence: 99%
“…Previous results demonstrate similar compounds in the essential oil of C. odorata leaf. This includes α-cadinol (2.19%), γ-cadinene (0.85%), δ-cadinene (3.5%), and germacrene D (2.1%) (Joshi 2013;Pitakpawasutthi et al 2016).…”
Section: Identification Of Chemical Constituentsmentioning
confidence: 99%
“…King & H. Rob is a perennial shrub (Asteraceae) (Suksamrarn et al 2004) that grows extensively until 3 m to 7 m in height (Joshi 2013). It is frequently identified as 'Siam' weed, and is locally known as kapal terbang.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation